MODEL RADY ZAKŁADOWEJ NA GRUNCIE POWSTAŃCZEGO ROZPORZĄDZENIA Z 1 SIERPNIA 1944 R. - Kijowski, Andrzej; Jankowiak, Jarosław (Wydział Prawa i Administracji UAM, 2005)
Numerous publications have been issued to mark the 60th anniversary of the outbreak of the Warsaw Uprising, offering a variety of viewpoints for this historical event. At the same time, many authors analysed various aspects of the Polish Underground State during the Second World War. Yet, the substantial legal accomplishments of this state, e.g. two Journals of Laws (Dzienniki Ustaw) issued by the State Authorities during the uprising, remain overshadowed. For that reason the following publication has been devoted to the analysis of one of the most fundamental accomplishments from that period, which is the model of company employee council in the light of the Regulation of the Polish Council of Ministers of 1 August 1944. The authors present the historical context of this regulation and normative constructs introduced in it. They also consider whether it would be possible to use it, at least partially, in the draft copy of the new Polish Labour Code.
MODEL OF COMPANY EMPLOYEE COUNCIL BASED UPON INSURRECTIONARY DECREE OF 1 AUGUST 1944